Diseño de productos turísticos para la diversificación de la oferta en el cantón Riobamba, provincia de Chimborazo. - Moncayo Trujillo, Andrés Francisco (2018)
This research project proposes “The Design of Tourism Products for diversification of the Offer of the Canton Riobamba” Chimborazo’s province; the main problem that arises is the deficient offer of the attractions, the lack of interest in the elaboration, promotion and commercialization of tourism products focused on the main and potential attractions existing in the Canton, this was done through investigative and field work, with the tourist servers and visitors of the Canton. It was decided to perform a situational diagnosis of the Riobamba’s tourism and its attractions using the official information delivered for the Riobamba’s GAD, the potentialities of tourism were known, based on the application of the interviews and surveys carried out considering the variables of the proposed topic choosing the options more chords to the demand found in the lines of cultural, ecotourism, sports, adventure, and community tourism, 4 products touristic were designed, the first one that can be done in family, maintains own aspects of the culture and the natural beauties, the second of the Nationality, you can know archeological sites, the third Adventure Tour around the Chimborazo, nearby tourist places and the Riobamba’s city, finally the adventure of the weekend that includes the paragliding service focused on the development of tourism, through the incentive that the tourist decides to stay or overnight for more than 1 or 2 days in the canton and consume the services available the Canton Riobamba.